Performance evaluation of solar PV mini grid system in Nepal: a case study Thabang and Sugarkhal - Karna, Sanjay Lal; Jha, Ajay Kumar; Yadav, Kishori; Kumar Mallik, Jiwan (Frontiers in Energy Research, 2024)
This article investigates the performance metrics of two solar mini-grid systems, Thabang Solar Mini-Grid (TSMG) and Sugarkhal Solar Mini-Grid (SSMG), based on secondary live data, collected from Renewable Energy for Rural Livelihood (RERL) and PVsyst software 7.4 spanning the years 2021–2023. Notably, the highest irradiance levels were recorded in April for both TSMG and SSMG. TSMG exhibited an energy generation of 83.206 MWh/year in 2021 and 112.140 MWh/year in 2022, with a peak sun hour (PSH) of 5.5 h. Conversely, SSMG energy generated 64.14 MWh/year in 2021 and 68.79 MWh/year in 2022, with a PSH of 5.7 h. The capture loss of SSGM recorded 0.239 kWh/day to 3.322 kWh/day in 2021 and 0.082 kWh/day to 2.086 kWh/day in 2022. Also, the capture loss of TSGM recorded 1.573 kWh/day to 5.011 kWh/day in 2021 and 0.470 kWh/day to 4.261 kWh/day in 2023. The efficiency of SSMG is consistently higher efficiency compared to TSMG. The capture factor of SSMG increased from 9.76% in 2021 to 10.47% in 2022, while of TSMG 6.33% in 2021 to 8.53% in 2023. The findings provide valuable insights into the comparative performance of these solar mini-grid systems, contributing to the optimization and improvement of solar energy generation in diverse environmental conditions.